DEVELOPMENT OF A MOBILE APPLICATION FOR LEARNING BASIC TECHNOLOGY CONCEPTS IN UPPER-BASIC SCHOOLS - Abdulrahman, Mohammed Rabiu; Soetan, Aderonke Kofo; Onojah, Amos Ochayi; Aderoju, Adekola Musiliu (Sanata Dharma University Yogyakarta, 2024)
Despite the quick advancements in technology, students still have to attend demanding in-person classes. However, students can get curriculum-based instruction remotely via mobile devices. As a result, a mobile application was developed for usage in Nigerian upper basic schools using the ASSDURE (Analysis, Statement of Objectives, Design, Development, Utilization, Response, and Evaluation) paradigm. This study's model-type design and development research included a single-group pre-test-post-test design. The population consisted of students from upper-basic schools in Nigeria, specifically from upper-basic school two. Findings indicated that the developed application improved students' academic performance, as evidenced by their respective pre- and post-test performance percentage scores of 53.0% and 66.4%. The mobile app received positive evaluations from experts in instructional design, basic technology, and educational technology, with scores of 85%, 79.7%, and 88.3%, respectively. The study's conclusions indicate that the developed application is appropriate for educational purposes. It is inferred that pupils will perform better academically. Thus, among other things, it was proposed that mobile applications be included in basic technology instruction.